Comparison between Peruvian regulations and foreign regulations related to the durability of the concrete - Paula Nicole Dongo Gómez (2019)
In the present investigation, a comparison was made between the Peruvian, Argentine, Bolivian and Brazilian standards of structural concrete, in order to analyze its content regarding the durability of the concrete and find possible shortcomings of the current Peruvian legislation. The durability of concrete is the ability of this material to withstand the action of various agents that modify its properties. This aspect has become important in recent years because its consideration in the design of structures could prevent problems such as cracking, corrosion, carbonation and others, which could put at risk the functionality of vital constructions in society, besides causing costs for repair and in the worst cases, reconstruction. To make a durable concrete, an analysis of the type of exposure in which the projected structure will be found is made, so that measures can be taken to mitigate negative effects on it. The consulted standards consider different parameters for each type of exposure, which have different nomenclature. Some of the parameters found are: compressive strength of the concrete, water/ cement ratio, type of cement, depth of penetration and absorption speed. The data found in the analyzed standards are congruent with each other, in some cases, they are the same; this is because some standards have been developed based on the US standard. We also found parameters specific to each country, being one of these cases the water penetration depth test, regulated only in Argentina.